Resilience as determinants of teaching efficacy among special education pre-service teachers - Abdul Jalil, Amalina Ulya; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The purpose of this study is to discover the relationship between resilience with teaching efficacy among special education pre-service teachers. The study also proposes to determine the level of four dimension of resilience in theme acceptance, support of self-awareness, conversion and connectedness and teaching efficacy of personal teaching efficacy, general teaching efficacy and special education competencies. The samples are 194 of special education pre-service teachers in the Malaysia public universities that offer the teacher training of special education course. The descriptive analysis is carried out to fulfil the objectives of study in determining the level. The Pearson correlation is conducted to determine the relationship between resilience with teaching efficacy among special education pre-service teachers. Regressions were used to predict the pre-service teacher teaching efficacy based on the aspects of resilience. The finding showed the moderate levels of resilience and teaching efficacy. The Pearson correlation generally shows that resilience has a positive significant relationship with teaching efficacy. The regression analysis shows that resilience in conversion as essential predictors for teaching efficacy. The implication of this study remarks a clear indication which special education pre-service teachers should perceive resilience, towards and belief regarding efficient professional performance.